Control of electrical drives - Leonhard, Werner, 1926- (Berlin : Springer, 2001)
Electrical drives play an important part as electromechanical energy converters in transportation, materials handling and most production processes. This book, now in its revised, enlarged, and updated third edition, presents a unified treatment of complete electrical drive systems, including the mechanical parts, electrical machines, and power converters and control. Since it was first published in 1985 the book has found its way onto many desks in industry and universities all over the world. The text provides the reader with a general view of the field of controlled electrical drives, which are maintaining and extending their importance as the most flexible source of controlled mechanical energy. Special emphasis is placed on the new developments in three-phase AC drives
Keywords: Automatic control; Electric driving; Elektromotorische aandrijving; Regeltechnieken